Improving Nutrition Through Multisectoral Approaches - World Bank (Washington, DC, 2013)
The objectives of the nutrition sensitive social protection are: 1) target activities to the most nutritionally vulnerable populations such as pregnant women and children less than 24 months; 2) include nutrition education and counseling activities within social protection interventions to increase household awareness of care giving and health seeking behaviors; 3) integrate nutrition services into Social Protection (SP) interventions; and 4) reduce the acute and long-term negative financial impacts of external financial, price, and weather shocks by scaling up programs in times of crises and by targeting shock-affected areas. This guidance note aims to assist World Bank and other program staff in maximizing the nutrition impacts of health investments and policies, with a special focus on under nutrition among women and children under two years of age in developing economies. The strong synergies between health and nutrition are highlighted and key evidence-based nutrition interventions that can be delivered through the health sector are presented. Implementing such interventions is cost-effective and can achieve large reductions in morbidity, mortality, and under nutrition, furthering health sector goals. The main nutrition-related objectives that fall within the health sector are outlined in the box below. Evidence-based interventions to address each objective, along with implementation considerations, are presented as options to integrate nutrition interventions in health investment and policies. To date, the scaling up nutrition framework has been endorsed by over 100 partners worldwide and 30 developing countries have committed to scaling up nutrition. Leaders of these countries are prioritizing nutrition as an investment in their people's growth, and recognizing nutrition as an investment in economic and social development to strengthen their nations.